Samuel Chiles Mitchell papers - Mitchell, Samuel Chiles, 1864-1948.
Correspondence, speeches, lectures, articles, poetry, financial records, clippings, printed matter, photographs, and other papers relating primarily to Mitchell's work as president of the University of South Carolina. Subjects include education in the South and disputes between Mitchell and Coleman Livingston Blease, governor of South Carolina. Includes memoranda, reports, and records relating to the administration of the Peabody Education Fund. Correspondents include Charles Francis Adams, Samuel Palmer Brooks, Reverend J.J. Hall, Albert Bushnell Hart, Hamilton Holt, Walter Hines Page, George Foster Peabody, Sir Horace Curzon Plunkett, and George E. Rives.
College president and educator.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Adams, Charles Francis, -- 1835-1915 -- Correspondence; Blease, Coleman Livingston, -- 1868-1942.; Brooks, Samuel Palmer, -- 1863-1931 -- Correspondence; Hall, J. J., -- Reverend -- Correspondence; Hart, Albert Bushnell, -- 1854-1943 -- Correspondence; Holt, Hamilton, -- 1872-1951 -- Correspondence; Page, Walter Hines, -- 1855-1918 -- Correspondence; Peabody, George Foster, -- 1852-1938 -- Correspondence; Plunkett, Horace Curzon, -- Sir, -- 1854-1932 -- Correspondence; Rives, George E. -- Correspondence; Peabody Education Fund; University of South Carolina; Universities and colleges -- South Carolina; Education -- Southern States; College presidents; Educators